Populism – a Bane for India? - , Noyonika Nag (Archives of Current Research International, 2025)
The demographics and growth of India have made it an epicentre in emerging world economics. In the face of prevailing geopolitics, trade frictions and race for technology dominance, India’s trajectory has a meaningful impact - not only on global commerce, but also emerging world pre-eminence. This paper examines the direction of India's current fiscal course, socio-economic impact of resource alignments, and the potential fallouts of any misdirected priorities. It concludes that India’s tilting balance towards politically benefiting populism constricts the fiscal space for priming the economy to growth, thereby increasing downside risks to revenues and deficits. The only solution is better targeting of populist expenditure, to allow much needed capital infusion into development sectors.